Analisis Peran Valuasi Saham (PER) dalam Memediasi Pengaruh Tingkat Kesehatan Rumah Sakit terhadap Harga Saham - Winata, Ardi (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study analyzes the mediating role of stock valuation using the Price to Earnings Ratio (PER) on the relationship between hospital financial health and stock prices among healthcare companies listed on the Indonesia Stock Exchange (IDX) during 2018–2023. Financial health is measured using the Altman Z-Score, while stock price is represented by annual closing prices. The study employs a quantitative explanatory design with purposive sampling, resulting in 42 observations from 7 hospital issuers. Data were analyzed using WarpPLS to examine both direct and indirect effects. The results indicate that hospital financial health has a significant positive effect on stock prices and a significant positive effect on stock valuation (PER). However, PER does not have a significant effect on stock prices. Furthermore, PER is found not to mediate the relationship between hospital financial health and stock prices. These findings imply that investors respond more strongly to fundamental financial health signals than to valuation indicators such as PER in the hospital industry. The study contributes to the literature on financial distress, valuation, and market reactions in the healthcare sector and provides practical insights for investors, hospital management, and policymakers.